Traumatic rupture of an ovarian teratoma - Case report and review of the literature - Avital Yohann; Constance W. Lee; Saleem Islam (Elsevier, 2017)
Traumatic rupture of a cystic ovarian teratoma is extremely rare and has not been reported in a child. The free fluid can lead to diagnostic confusion for a ruptured viscus.